THE IMPLEMENTATION OF COUNSELLING MANAGEMENT AT STATE ISLAMIC JUNIOR HIGH SCHOOL – 3 (MTsN 3) DELI SERDANG - Sukri, Nada; Lubis, Saiful Akhyar; Lubis, Lahmuddin (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2025)
The research objective is to find out the Management Implementation of Student Counseling Services Planning, to know the Management Implementation of Student Counseling Services Organizing, to know the Management Implementation of Student Counseling Services Implementation and to find out the Management Implementation Evaluation of Student Counseling Services in MTsN 3 Deli Serdang. The research method used is a qualitative phenomenological research method. The research site is at MTsN 3 Deli Serdang, and the research period is July 12, 2019, to October 12, 2019. Data collection techniques using interviews, observation, and documentation. Data analysis techniques using data reduction, presentation and drawing conclusions. The technique of guaranteeing the validity of the data is done by observing diligence and triangulating the data. The results of this study are: Management Implementation of student counseling services in MTsN 3 Deli Serdang seen from; Counseling service planning has conducted a work plan coordination meeting which is archived as a guidance for one year lesson counseling service. The implementation of counseling services can be seen from the agreement, summons and case books of students which are still neatly stored. Evaluation of counseling services is seen through timesheet and supervision conducted by the principal every two months.             Keywords: Implementation, Management, Counselling services.